Origins and developmental paths of medical conditions from mid-childhood to mid-adolescence in Australia: The early-life adverse conditions and lasting effects - Lan Nguyen; Luke B. Connelly; Stephen Birch; Ha Trong Nguyen (Global Labor Organization (GLO), 2025)
This study investigates the medical condition of Australian children aged 4 to 14 years and the impact of prenatal and early-life conditions on these health conditions, using a large national data set (n=4,122) with 15 years of follow-up. Consistent with the developmental origins of health and diseases hypothesis and the life-course models of health, the in-utero environment and parental financial hardship during pregnancy and shortly after birth play a significant role and have a lasting impact on the medical conditions of children. These significant effects are not reduced by controlling for child, family, and neighbourhood characteristics. The impact of improvements in family income when the child is aged 4 to 14 years does not compensate for the impact of health disadvantages in the prenatal and postnatal period.
Keywords: I14; J13; 330; Early Life Conditions; Child Development; Panel Data; Australia